Experimental Study of Solubility of Water in Liquid Organic Hydrogen Carriers - Aslam, Rabya; Müller, Karsten; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2015)
Liquid organic hydrogen carriers (LOHC) are one of the potential candidates to assuage the problem of hydrogen storage. Prior to the storage step, hydrogen produced from electrolysis can contain a significant amount of water, which can lead to the formation of an undesired two-phase system in the LOHC storage tanks. In this work, solubility of water in potential liquid organic hydrogen carriers (toluene, dibenzyltoluene, and N-ethylcarbazol) in their hydrogenated and dehydrogenated forms as well as mixtures of these forms have been measured within the temperature range of (293 to 343) K. The solubility of water in LOHC materials is found to increase with temperature. This effect has been correlated using the Tsonopoulos and Wilson equation. Furthermore, various thermodynamic parameters such as Gibbs free energy, enthalpy, and entropy of dissolution were estimated based on the solubility data using the van't Hoff equation.